Penerapan Model Project Based Learning pada Praktikum Biokimia untuk Meningkatkan Keterampilan 4C - Ekaputra, Firdiawan (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
The purpose of this study was to determine whether there was an increase in students' 4C skills in biochemistry practicum with the application of the project-based learning model. The design used in this study is a pre-experimental design with one class of research samples. The samples used in this study were students of the University's Chemistry Education Study Program who took the 2023/2024 Biochemistry Practicum course in class R-001. The data collection technique in this study used a questionnaire instrument. The questionnaire instrument was used to obtain 4C skills data. Data on 4C skills were analyzed using paired sample t-test. The application of the project-based learning model in biochemistry practicum resulted in an increase in students' 4C skills by 0.00. Based on the results of the study, it can be concluded that there is an increase in students' 4C skills in biochemistry practicum with the application of the project-based learning model